Pengaruh Motivasi Kerja Dan Pembayaran Tunjangan Penghasilan Pegawai (TPP) Terhadap Kinerja Pegawai Pada Kota Palangka Raya - Yuniartie, Yuniartie; Normuslim, Normuslim; Muslimah, Muslimah; Mahsuni, Abdul Wahid (UNIVERSITAS ISLAM MALANG, 2024)
AbstractIn formulating policies that will be taken into consideration by the Regional Secretary and Mayor, high levels of employee performance capability and credibility are required. The aim of this research is to determine and analyze the influence of work motivation and payment of employee income allowances on employee performance which is positive and partially significant as well as the influence of work motivation and payment of income allowances on employee performance simultaneously at the Palangka Raya City Education Office.The method used in this research uses quantitative research because it tests the hypothesized theory using primary data through questionnaires. The sample used refers to an accidental sampling technique of 69. Hypothesis testing uses multiple regression data analysis techniques assisted by using the SPSS version 25 program application.The results of this research showed that the work motivation variable and the employee income allowance variable had a positive and significant partial effect on employee performance and the influence of the work motivation variable and the employee income allowance variable had a significant joint (simultaneous) effect on employee performance at the Palangka Raya City Education Office. Keyword: Work Motivation, Benefits, Employee Performance